2014
DOI: 10.1027/0227-5910/a000271
|View full text |Cite
|
Sign up to set email alerts
|

Physical Illness and Suicide Risk in Rural Residents of Contemporary China

Abstract: Physical illness is an important risk factor for suicide in rural residents of China. Efforts for suicide prevention are needed and should be integrated with national strategies of health care in rural China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
6
21
0
Order By: Relevance
“…Elderly suicide victims were more likely to experience life events, have an unstable marital status, physical diseases, and mental disorders. These risk factors have also been reported in previous studies [24][25][26]. The elderly were living in worse conditions and this seemed to increase the risk of suicide.…”
Section: Discussionsupporting
confidence: 80%
“…Elderly suicide victims were more likely to experience life events, have an unstable marital status, physical diseases, and mental disorders. These risk factors have also been reported in previous studies [24][25][26]. The elderly were living in worse conditions and this seemed to increase the risk of suicide.…”
Section: Discussionsupporting
confidence: 80%
“…We also found that the prevalence rate of mental disorder was 47.4% in the suicide cases. Some other studies also showed that mental disorders can be found about 40–70% of all suicides in China . However, the prevalence rate of mental disorder among suicides in the West countries was over 90% .…”
Section: Discussionmentioning
confidence: 92%
“…Some other studies also showed that mental disorders can be found about 40-70% of all suicides in China. 5,34 However, the prevalence rate of mental disorder among suicides in the West countries was over 90%. 35 One possible explanation for the differences is that suicides in China are more strongly related to social stresses or cultural differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between the number of physical illnesses and both nonfatal suicidal behaviour and suicide were shown in a Hong Kong-based study (Tsoh et al., 2005 ). Increased odds of suicide were found among older adults with one and two physical illnesses in a Chinese study (Jia, Wang, Xu, Dai, & Qin, 2014 ).…”
Section: Resultsmentioning
confidence: 99%